Population status, nesting habitat selection and conservation threats of lesser adjutant stork (Leptoptilos javanicus) in the eastern lowlands of Nepal - Karki, Santosh; Thapa, Tej Bahadur (Conservation Science, 2013)
Aim This research examines the status of distribution, nesting habitat selection and conservation threats of lesser adjutant storks. Location Eastern Nepal Materials and Methods Direct observation along line transects method was used to determine population status, distribution and nesting habitat preference of storks in different habitats of the study area. Questionnaire surveys to local people drawn randomly were used to study the socio-cultural dimensions of lesser adjutant storks conservation. Key findings There were a total of 98 individuals in pre-breeding and 240 individuals of lesser adjutant stork in post-breeding periods (94 chicks and 146 adults) in the study area. On average, there were 1.29 chicks per nest. Bombax ceiba and Adina cordifolia were found to be the most preferred nesting trees for lesser adjutant storks. Habitat preference of lesser adjutant storks revealed that colonies were more likely to occur in farmlands and swamps. All the nests of lesser adjutant storks were found on trees above 30 m height, the average tree height was 42.5 ± 6.8 m and the average nest height was 34.4 ± 4.3 m. Questionnaire surveys revealed that people were not aware about conservation of lesser adjutant storks. More than 80% of respondents (n=145) opined that forest destruction was the most serious threat to storks followed by human disturbance (79%), poaching (73%), pesticide use (52%), and urbanization/industrialization (43%). Conservation implications Protection of nesting tree species such as Bombax ceiba and Adina cordifolia should be given a high priority for the conservation of storks in the eastern Nepal. Conservation education programs to control excessive pesticides in the rice fields should also be carried out in the region. DOI: http://dx.doi.org/10.3126/cs.v1i1.8581 Conservation Science 2013 1(1), 27-35